PENYUSUNAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN MICROSOFT EXCEL PADA UMKM TOKO XYZ PERIODE MARET 2024 - Damiyana, Damdam; Enggun Gunawan; Anggraini Safitri (DIVERSITY: Journal of Multi Science Linearity, 2024)
The author sees obstacles that are often experienced by MSME actors, namely the absence of correct and unstructured records for their financial reporting. The purpose of this study is to find out how to record transactions, prepare financial reports, and how to present financial reports at TOKO XYZ for the March 2024 period. The research method used is a qualitative descriptive method to be able to describe, describe, and explain the actual events of the objects studied based on the situation and conditions when the research was conducted at Toko XYZ. Research data was obtained through field studies and literature studies in the form of observations and documentation. Based on the results of observations made by the author, it can be concluded that preparing financial reports using Microsoft Excel can make it easier and more efficient.